(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need for higher success in academic achievement of students in biology has always been the concern of science teachers, educational assessors and evaluator. It is necessary to experiment more student-centre methods of teaching. This study, therefore, ascertain the effects of brainstorming and think-pair-share teaching strategies when compared with the usual conventional teaching method. Two research questions were answered and two corresponding hypotheses were tested. The quasi-experimental research design was employed. One hundred and thirty-nine senior secondary school students were sampled. The biology achievement test (BAT) with multiple choice questions was used as the instrument for data collection. The BAT was subjected to face and content validity, while Kuder-Richardson method was used for the reliability, which yielded a coefficient of 0.71. data were collected as pre-test, post-test, and delayed post-test. Mean, standard deviation, and analysis of covariance were used as statistic tools. Findings revealed that students showed higher academic achievement scores with the think-pair-share and brainstorming strategies than the conventional method. Nevertheless, no significant difference was found between the students taught biology with brainstorming and think-pair-share strategies. The implication is that students will report higher academic achievement when student-centre methods are employed in teaching biology in secondary school.